2018
DOI: 10.5487/tr.2018.34.1.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adipocyte Differentiation by Anthocyanins Isolated from the Fruit ofVitis coignetiaePulliat is Associated with the Activation of AMPK Signaling Pathway

Abstract: Anthocyanins are naturally occurring water-soluble polyphenolic pigments in plants that have been shown to protect against cardiovascular diseases, and certain cancers, as well as other chronic human disorders. However, the anti-obesity effects of anthocyanins are not fully understood. In this study, we investigated the effects of anthocyanins isolated from the fruit of Vitis coignetiae Pulliat on the adipogenesis of 3T3-L1 preadipocytes. Our data indicated that anthocyanins attenuated the terminal differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 37 publications
0
34
0
Order By: Relevance
“…Activation of AMPK signalling pathway acts as a sensor of cellular energy status, and inhibition of preadipocyte differentiation and adipogenesis through increased phosphorylation of its substrate, acetyl-CoA carboxylase (ACC) [22]. Interestingly, a widely prescribed drug for type 2 diabetes-metformin inhibits hepatic gluconeogenic programme by activation of AMPK pathway [23] long-term usage of which may, therefore, have negative consequences on normal adipose physiology.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Activation of AMPK signalling pathway acts as a sensor of cellular energy status, and inhibition of preadipocyte differentiation and adipogenesis through increased phosphorylation of its substrate, acetyl-CoA carboxylase (ACC) [22]. Interestingly, a widely prescribed drug for type 2 diabetes-metformin inhibits hepatic gluconeogenic programme by activation of AMPK pathway [23] long-term usage of which may, therefore, have negative consequences on normal adipose physiology.…”
Section: Gene Expression Analysismentioning
confidence: 99%
“…Our results in 3T3-L1 are in accordance with other authors who have used these cells. Treatment with 140 µg/mL GSPE at the onset of differentiation reduced adipogenesis markers [ 7 ], while an inhibition of lipid content and adipogenic transcription factors was observed with a concentration of 100 µg/mL of anthocyanins extracted from Vitis coignetiae [ 8 ]. Unexpectedly, we obtained no differences in the lipid content of cells with CLA treatment, while other authors showed that 10 mg/L of CLA isomers, consisting principally of 41% c9, t11 and 44% t10, c12, inhibited proliferation of 3T3-L1 preadipocytes while promoting lipogenesis [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although adipocytes are the principal cells in WAT, it also includes a heterogeneous cell population called the stromal vascular fraction (SVF) [ 6 ]. Adipocytes have been extensively studied in vitro in the murine 3T3-L1 cell line, which is a good model to study the effects of particular compounds on adipocyte differentiation [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conventionally, AMPK is activated by an increase of AMP/ATP ratio via phosphorylation of its catalytic α subunit (AMPKα) at Thr172 in the case of environmental and cellular stress, such as heat shock, hypoxia, ischemia, exercise, and long‐term starvation, resulting in enhanced glucose uptake and fatty acid oxidation to re‐establish cellular energy homeostasis (Carling, ). In addition, it has been shown that AMPK plays a vital role in cell differentiation, which involves suppressing adipogenic differentiation while promoting osteogenic differentiation (Han et al, ; Qin et al, ). In the present study, berberine markedly increased AMPKα phosphorylation at Thr172 in a concentration‐dependent manner in porcine adipocytes (Fig.…”
Section: Discussionmentioning
confidence: 99%